2023
DOI: 10.1038/s41392-022-01219-0
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal dysbiosis exacerbates the pathogenesis of psoriasis-like phenotype through changes in fatty acid metabolism

Abstract: The intestinal microbiota has been associated with host immunity as well as psoriasis; however, the mechanism of intestinal microbiota regulating psoriasis needs to be demonstrated systematically. Here, we sought to examine its role and mechanism of action in the pathogenesis of psoriasis. We found that the severity of psoriasis-like skin phenotype was accompanied by changes in the composition of the intestinal microbiota. We performed co-housing and fecal microbial transplantation (FMT) experiments using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 70 publications
1
20
0
1
Order By: Relevance
“…17 Reactive oxygen species (ROS) generated by ultraviolet (UV) radiation can lead to skin barrier dysfunction, while sphingolipid-containing lacto-phospholipids can reduce skin barrier damage by regulating heme oxygenase-1 (HO-1) and reducing ROS levels through milk phospholipid-mediated activation of nuclear factor erythroid-2-related factor 2 (Nrf2). 18 Our study found acyl carnitine (CAR)-lipid acyl CoA under the action of carnitine lipid acyltransferase, and enter the matrix across the inner mitochondrial membrane to participate in oxidation 19,20 The decrease in fatty acids and complex phospholipids may be due to a dramatic decrease in 3-carbon intermediates (glycerol-based) in the glycolytic pathway, which generally provides the backbone for the synthesis of these lipids. 21 Palmitic acid, lauric acid and oleic acid in free fatty acids increase the release of antimicrobial peptides in the sebaceous glands, thus achieving an antimicrobial effect and preventing the entry of external harmful substances into the organism.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…17 Reactive oxygen species (ROS) generated by ultraviolet (UV) radiation can lead to skin barrier dysfunction, while sphingolipid-containing lacto-phospholipids can reduce skin barrier damage by regulating heme oxygenase-1 (HO-1) and reducing ROS levels through milk phospholipid-mediated activation of nuclear factor erythroid-2-related factor 2 (Nrf2). 18 Our study found acyl carnitine (CAR)-lipid acyl CoA under the action of carnitine lipid acyltransferase, and enter the matrix across the inner mitochondrial membrane to participate in oxidation 19,20 The decrease in fatty acids and complex phospholipids may be due to a dramatic decrease in 3-carbon intermediates (glycerol-based) in the glycolytic pathway, which generally provides the backbone for the synthesis of these lipids. 21 Palmitic acid, lauric acid and oleic acid in free fatty acids increase the release of antimicrobial peptides in the sebaceous glands, thus achieving an antimicrobial effect and preventing the entry of external harmful substances into the organism.…”
Section: Discussionmentioning
confidence: 97%
“…Fatty acids are oxidized through β‐oxidation to produce acetyl CoA, which is completely oxidized by the tricarboxylic acid cycle to produce CO2 and H2O and release energy. Fatty acid oxidation is divided into three stages, activation‐transfer‐oxidation and fatty acids need to be catalysed by lipid acyl CoA synthase to generate lipid acyl CoA first, then transported into mitochondria with the help of carnitine, and complete the transformation of lipid acyl CoA‐lipid acyl carnitine (CAR)‐lipid acyl CoA under the action of carnitine lipid acyltransferase, and enter the matrix across the inner mitochondrial membrane to participate in oxidation 19,20 The decrease in fatty acids and complex phospholipids may be due to a dramatic decrease in 3‐carbon intermediates (glycerol‐based) in the glycolytic pathway, which generally provides the backbone for the synthesis of these lipids 21 . Palmitic acid, lauric acid and oleic acid in free fatty acids increase the release of antimicrobial peptides in the sebaceous glands, thus achieving an antimicrobial effect and preventing the entry of external harmful substances into the organism 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, VEGF has emerged as a promising therapeutic target for psoriasis [27]. Studies have also demonstrated that alterations in fatty acid metabolism can exacerbate the pathogenesis of psoriasislike symptoms [28]. Additionally, lysophosphatidic acid, a simple phospholipid found in nature, has been implicated in the development of psoriasis [29].…”
Section: Discussionmentioning
confidence: 99%
“…Animal experiments have shown that abnormalities in lipid metabolism induced by a high-fat diet contribute to developing psoriasis, 16,21,22 and clinical studies have demonstrated abnormalities in lipid metabolism in patients with psoriasis. 17,23 However, the causal relationship between lipid metabolism and psoriasis remains unknown.…”
Section: Discussionmentioning
confidence: 99%